2005
DOI: 10.1093/cje/bei071
|View full text |Cite
|
Sign up to set email alerts
|

A Buddhist economic approach to the development of community enterprises: a case study from Southern Thailand

Abstract: This study was undertaken to observe the development process and key success factors in three community enterprises adopting a Buddhist economic approach to development. The enterprises were established by weavers, farmers and housewives from three communities in the south of Thailand. Data were obtained through in-depth interviews and observation with representatives of the groups and their supporters as they participated in community activities. Buddhist economics differs significantly from neoclassical econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 2 publications
0
37
0
Order By: Relevance
“…In addition, Bradley, Meyer, and Gao (2006) suggested that local entrepreneurs export to international markets by collaborating with large entrepreneurs to seek new target markets in foreign countries. Prayukvong (2005) suggested the key success factor in community enterprises is good decision-making by members of community enterprises and how to use the local wisdom of leaders and group members in their thinking process.…”
Section: Literature Reviews and Conceptual Frameworkmentioning
confidence: 99%
“…In addition, Bradley, Meyer, and Gao (2006) suggested that local entrepreneurs export to international markets by collaborating with large entrepreneurs to seek new target markets in foreign countries. Prayukvong (2005) suggested the key success factor in community enterprises is good decision-making by members of community enterprises and how to use the local wisdom of leaders and group members in their thinking process.…”
Section: Literature Reviews and Conceptual Frameworkmentioning
confidence: 99%
“…Welfare for an individual in this case has been translated in economics as "utility" which can be gained by having more material possessions. Wellbeing, for this approach, is an indirect effect from economic development (Prayukvong, 2005) while, SEA place humanity by focusing on the wellbeing as the centre of development. Wellbeing in this sense comprises of three dimensions: material, relational, and subjective (White, 2008).…”
Section: Concept Of Sufficiency Economy Approachmentioning
confidence: 99%
“…However, in the case of KKW, the dominant power is exerted by the temple, which is seen as a highly respectable institute in the community. The intention of the abbot to solicit only a onetime fee for the rent was based on his good intention toward local vendors, which in turn reinforces the role of the temple as a supporter of the community (Prayukvong, 2005). However, this practice impeded the management of the floating market and decreased the level of participation and involvement from the locals.…”
Section: Discussionmentioning
confidence: 99%